Molecular characteristics of multiple primary pulmonary nodules under a three-dimensional reconstruction model and relevant multi-omics analyses: a case report - Luo, Zhilin; Xiao, Yajie; Luo, Chengwen; Zhang, Liping; Zhou, Runquan; Zhao, Zhikun; Sun, Chao; Wu, Dongfang; Wang, Tianhu (Frontiers in Oncology, 2023)
Background: In addition to CT images and pathological features, lots of other molecular characters remains unknown about multiple primary lung cancer (MPLC) from intrapulmonary metastatic lung cancer (IPM). Case presentation: In this study, we reported an early-stage MPLC patient with both adenocarcinoma in situ (AIS) subtype and minimally invasive adenocarcinoma (MIA) subtype. The patient was diagnosed with more than 10 nodules and underwent precise surgery assisted by three-dimensional (3D) reconstruction at the left upper lung lobe. Whole-exome sequencing (WES) and multiple immunohistochemistry (mIHC) were performed to reveal the genomic profiling and tumor microenvironments of multiple nodules in this MPLC patient. Based on 3D reconstruction location information, we found that the genomic and pathological results of adjacent lymph nodes are quite different. On the other hand, PD-L1 expression and proportion of infiltrating lymphocytes in tumor microenvironments were all at low status and did not vary in adjacent lymph nodes. Additionally, maximum diameter and TMB levels was found to be significantly associated with CD8+ T cell proportion (p<0.05). Besides, CD163+ macrophages and CD4+ T cell proportion were higher in MIA nodules than in AIS nodules (p<0.05). This patient reached a recurrence free survival of 39 months. Conclusion: Generally, in addition to CT imaging and pathological results, genomic profiling and tumor microenvironments may facilitate identifying the potential molecular mechanisms and clinical outcomes in early-stage MPLC patients.